ANALYSES OF RADIATION OF ELECTROMAGNETIC WAVES IN THE HIGH-VOLTAGE AIR DUCT (150 kV) CONSTRUCTION ON HEALTH - Jayadipraja, Erwin Azizi (Public Health of Indonesia, 2017)
Background: High-voltage air ducts is the government program to supply electricity needs. However, in practice, obstacles have been identified in the form of rejection from the community due to the outstanding issues that high-voltage air ducts have an impact on health.Aim: This research aims to analysis the magnitude of electromagnetic wave radiation of high-voltage air ducts construction on health.Methods: The study was conducted by measuring electromagnetic wave radiation prior to high-voltage air ducts (150 kV) construction and predicting the amount of radiation generated after this operation and its impact on health.Result: The field measurement result showed that the highest strength of magnetic field in the absence of construction and operation activity of high-voltage air ducts 150 kV was 0.00085 mT and the highest electric field was 0.004241251 V/m. The results of the magnetic field strength analysis showed that the highest strength of magnetic field and electric field when the high-voltage air ducts is completed and operated was magnetic field of 0.00415 mT and electric field of 38.4 V/m. The value was far lower than the standard limits recommended by IRPA / INIRC, WHO1990 and SNI 04-6950-2003. The allowed electric field strength is 5 kV / m and the allowed magnetic field strength is 0.1 mT.Conclusion: Electromagnetic wave radiation of High-Voltage Air Ducts is not exceeded the allowed limit, so it will not cause a direct risk to health.